Design and implementation of a Dispatch Management System for the control of loading and hauling equipment using mobile signal communication at the Summa Gold Corporation SAC mining unit - Alfaro, Antony (2022)
Nowadays, companies are applying different technologies to support the development of their production processes; one of the sectors is mining, where technology is applied in its different stages and production processes. In this paper, a new design of a control system for loading and hauling equipment was developed by means of a Dispatch management system supported by mobile signal technology, GPS, technological equipment (Tablets) that were used for the creation of the system and by means of the Scrum methodology, which allowed the planning of each phase of the design, to have a better control in real time of the work performed by each loading and hauling equipment in the mining unit of the company Summa Gold Corporation SAC, in order to have a much more accurate information of the work being done, generating value in the company. As a result, it was possible to efficiently manage the times of the operation's equipment, as well as to reduce costs by efficiently operating the mine's resources, since productivity was increased and unproductive times were eliminated.